2009
DOI: 10.1186/1471-2415-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in Tehran province: a population-based study

Abstract: Background: To determine the prevalence and characteristics of diabetic retinopathy (DR) among Iranian patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
67
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 36 publications
18
67
5
Order By: Relevance
“…Prevalence of CSME increased with increasing age of diabetics. Similar observations were evident in studies which were done in the past [16][17][18]. Associated hypertension is a known risk factor for development of diabetic retinopathy [19].…”
Section: Resultssupporting
confidence: 85%
“…Prevalence of CSME increased with increasing age of diabetics. Similar observations were evident in studies which were done in the past [16][17][18]. Associated hypertension is a known risk factor for development of diabetic retinopathy [19].…”
Section: Resultssupporting
confidence: 85%
“…Nevertheless, our findings are supported by a growing body of evidence. Indeed, insulin use was an independent predisposing factor for DR (OR 32.71; 95% CI, 4.11-259.85) in the study by Javadi et al (15), similarly as in the SN-DREAMS III cross-sectional study (OR 3.59; 95% CI, 1.41-9.14) (16). Consistent with those findings, a large retrospective cohort study including 85,214 T2DM patients identified insulin treatment as an independent risk factor for DR (hazard ratio 2.03; 95% CI, 1.89-2.18; P<0.001) (17).…”
Section: Discussionmentioning
confidence: 82%
“…Diabetes mellitus is becoming a major health issue by presenting two major problems namely increase in the number of diabetics and increase in the prevalence of disastrous long term complications resulting in amputations, cardiovascular disorders, end stage renal [15][16][17][18][19][20] disease and blindness [1]. DR is the leading cause of blindness in long-standing patients of diabetes mellitus [9] and is responsible for ~ 10,000 new blind cases each year in USA alone [17] between the ages of 20 to 75 years [21].…”
Section: Discussionmentioning
confidence: 99%
“…DR is the leading cause of blindness in long-standing patients of diabetes mellitus [9] and is responsible for ~ 10,000 new blind cases each year in USA alone [17] between the ages of 20 to 75 years [21].…”
Section: Discussionmentioning
confidence: 99%